IgA nephropathy with monotypic IgA-κ deposits: a case report and literature review - Li, Xiao-Ying; Xie, Guang-Liang; Chen, Bo; Zhang, Ji; Chen, Jian-Sheng; Ding, Xiao-Kai (Frontiers in Medicine, 2025)
IgA nephropathy (IgAN) is an immune complex-mediated glomerulonephritis characterized by predominant IgA deposition in the mesangial region, typically exhibiting polyclonal IgA deposits (co-dominance of κ and λ light chains). However, a few studies have reported IgAN cases with monotypic IgA deposition in glomeruli on renal immunofluorescence, predominantly IgA-λ, while IgA-κ deposition is rare. The pathogenesis, pathological features, and prognosis of IgA-κ monotypic deposition remain poorly understood. Here, we report a case of IgAN with monotypic IgA-κ deposits. The patient presented with microscopic hematuria and non-nephrotic range proteinuria and normal renal function. The renal histopathology revealed mild mesangial hypercellularity with segmental endocapillary proliferation. Both frozen and paraffin immunofluorescence showed monotypic IgA-κ deposition and C3 clumps deposition in mesangial region. Electron microscopy showed electron dense deposition in mesangial region, but no abnormal deposition of monoclonal light chain was observed by immunoelectron microscopy. After 12 months of follow-up, the patient was treated with maximal tolerated doses of renin-angiotensin system inhibitors combined with Nefecon, the patient’s urine protein decreased significantly and renal function was stable, and no hematological disorders were found during the follow-up. Therefore, IgAN with monotypic IgA-κ deposits shares similar clinicopathological features and prognosis with IgAN with polyclonal IgA deposits, suggesting that they may belong to the same disease spectrum. Moreover, IgAN with monotypic IgA-κ deposits and proliferative glomerulonephritis with monoclonal IgA deposits (PGNMID) share similarities in pathological manifestations. Therefore, rigorous monitoring of hematological indices in IgAN patients with monotypic IgA-κ deposits is essential to remain vigilant against misdiagnosis or missed diagnosis of early-stage PGNMID.